2020
DOI: 10.3390/cancers12061453
|View full text |Cite
|
Sign up to set email alerts
|

DSCAM-AS1-Driven Proliferation of Breast Cancer Cells Involves Regulation of Alternative Exon Splicing and 3′-End Usage

Abstract: DSCAM-AS1 is a cancer-related long noncoding RNA with higher expression levels in Luminal A, B, and HER2-positive Breast Carcinoma (BC), where its expression is strongly dependent on Estrogen Receptor Alpha (ERα). DSCAM-AS1 expression is analyzed in 30 public datasets and, additionally, by qRT-PCR in tumors from 93 BC patients, to uncover correlations with clinical data. Moreover, the effect of DSCAM-AS1 knockdown on gene expression and alternative splicing is studied by RNA-Seq in MCF-7 cells. We confirm DSCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…Higher expression of DSCAM-AS1 was significantly correlated with poor survival of ER + breast cancer patients. During the preparation of this manuscript, Elhasnaoui et al 65 reported a re-analysis of DSCAM-AS1 effect on survival in BRCA, resulted in a conclusion similar to ours. Intriguingly, in lung cancer, DSCAM-AS1 showed distinctive expression in LUAD but was almost undetectable in LUSC ( Figure S1 B).…”
Section: Discussionsupporting
confidence: 83%
“…Higher expression of DSCAM-AS1 was significantly correlated with poor survival of ER + breast cancer patients. During the preparation of this manuscript, Elhasnaoui et al 65 reported a re-analysis of DSCAM-AS1 effect on survival in BRCA, resulted in a conclusion similar to ours. Intriguingly, in lung cancer, DSCAM-AS1 showed distinctive expression in LUAD but was almost undetectable in LUSC ( Figure S1 B).…”
Section: Discussionsupporting
confidence: 83%
“…While mutations occurring from the 5′-end up to the middle of the LINC-HELLP are likely to cause loss of partner protein interactions, those at the far 3′-end increase their binding [ 120 ]. Among a cohort of breast cancer-associated and oestrogen-regulated lncRNAs, DSCAM-AS1 has been recently found to be associated with tumor progression and tamoxifen resistance [ 121 ]. Researchers found over 2085 splicing events regulated by DSCAM-AS1 , including alternative polyadenylation sites, 3′ UTR shortening and exon skipping events.…”
Section: Lncrnas Regulate Pre-mrna Splicing By Modulating the Actimentioning
confidence: 99%
“…Researchers found over 2085 splicing events regulated by DSCAM-AS1 , including alternative polyadenylation sites, 3′ UTR shortening and exon skipping events. DSCAM-AS1 affects target gene expression and causes changes in the AS by interacting with hnRNPL which appears to mediate the exon skipping and 3′ UTR usage by a mechanism not yet fully elucidated [ 121 ].…”
Section: Lncrnas Regulate Pre-mrna Splicing By Modulating the Actimentioning
confidence: 99%
See 1 more Smart Citation
“…By investigating the functions of DSCAM-AS1 (Down Syndrome Cell Adhesion Molecule antisense 1)—a lncRNA overexpressed in invasive breast cancers—De Bortoli and coworkers reported that the lncRNA, besides affecting global gene expression and producing changes in the AS of its targets, influences polyadenylation by regulating the alternative 3′ UTR usage of 360 genes [ 30 ]. These changes in the early steps of the post-transcriptional regulation of gene expression appear to depend on the interaction between DSCAM-AS1 and the nucleoplasm-enriched RBP hnRNPL [ 30 ].…”
Section: Lncrnas Rbps and Regulation Of Pre-mrna Processingmentioning
confidence: 99%